(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر التجارة الخارجية اليوم معيار تطور الدول وتوازنها في تحقيق احتياجاتها وتصدير البضائع إلى العالم فالتجارة الخارجية هي التي تحكم بالأرقام على اتجاه تأثير فعاليات مختلف السياسات الداخلية والخارجية إذ إن هيكل التجارة الخارجية يتجدد وفقا للبنيان الاقتصادي للبلد ، فحيث تشكل الزراعة القطاع الإنتاجي الرئيس في الاقتصاد القومي ، فإن هذا البلد يصدر المنتجات الأولية والزراعية ويستورد سلع الاستهلاك والإنتاج ، هذا من ناحية ، ومن ناحية أخرى ، فإن التغير الهيكلي للاقتصاد القومي الذي يرافق عملية التنمية الاقتصادية ، لا بد أن يؤدي إلى تغير هيكلي في التجارة الخارجية سواء في الصادرات أو الواردات. لذلك سنبحث في تطور التجارة الخارجية في سورية من خلال دراسة تطور عناصر التجارة الخارجية الأساسية الصادرات والواردات، التوزع الجغرافي الذي يحدد العلاقة الاقتصادية مع دول العالم الخارجي، بالإضافة إلى دراسة الميزان التجاري الذي ظل يعاني من عجز دائم عندما يتم استبعاد الصادرات النفطية من إجمالي الصادرات السلعية، الأمر الذي يعرِّض الاقتصاد السوري لتقلبات دورية واسعة بسبب طبيعة كل من الطلب والعرض التي تتميز بقلة المرونة في الأجل القصير مما يساعد على تغيير في أسعار المنتجات الأولية بالأسواق العالمية. The foreign trade is considered today the parameter for ensuring the development and balance of countries, to satisfy the internal needs, and export goods to the world . So foreign trade controls directions of numbers, towards affecting and activating, the different internal and external policies. However, the structure of foreign trade is determined by the economical report of the country, where the agricultural sector is the main one in national economy, so that this country exports the ore materials and agricultural productions, and imports consumer goods, and production needs, on the other hand, that the structural changes it national economy associated with economical development processes would lead to structural changes foreign trade affecting both exports and imports . This paper studies exterior trade in Syria through the study of the development of its main component of exports and imports as well as geographic distribution which specifies the economic relation ship with the countries of the outer world In addition the paper studies the balance of trade which has remained suffering of a permanent deficiency when the oil exports has been excluded from the total exports of goods .This matter exposes the Syrian economic for wide periodical turns due to the nature of supply and demand which is choric Teri zed by less of flexibility in the short – term this will help in the change of the prices of the raw products in the universal markets.